Internet use in patients with cardiovascular diseases: Bad Berka Cross‐Sectional Study (BABSY). Issue 10 (20th September 2013) - Ohlow, M.‐A.; Brunelli, M.; Lauer, B.
Summary Background Internet has become a significant resource for dissemination of medical information. We sought to investigate prevalence and usage patterns of Internet access among consecutive patients with cardiovascular diseases. Methods A cross‐sectional study was performed using a questionnaire as study tool. Among patients with Internet access, the type of health information sought and the impact of these on daily life were assessed. Results Of 1063 patients invited to the study, 1000 patients [68% male gender, mean age 66 ± 11 years (range 27–83 years)] agreed to complete the questionnaire. 216/1000 (21.6%) used Internet to obtain information related to their disease. The patient education was graded as: low (15%), medium (66%) and high (19%). Reasons for Internet use were as follows: 24‐h availability 142/216 (65.7%); free of charge 58/216 (26.9%); and anonymity 50/216 (23.2%). Younger (≤ 66 years) age (35.2% vs. 15.3%; p = 0.0001), male gender (24.6% vs. 15.4%; p = 0.001) and higher education level (49.4% vs. 16.1%; p = 0.001) were significantly associated with Internet use. 30.6% (66/216) of Internet users changed their individual health behaviour attributable to information found on the Internet. However, this was not related to age, gender or level of education (p = 0.5, p = 0.6 and p = 0.4, respectively). Patients without Internet use obtain health information mainly from the pharmacist (62%) or from their treating physician (58%). Conclusions A relevant number of patients with cardiovascular disease access the Internet for health information. The impact of such information on health‐related behaviour in daily life was low.